Strategic Communication Practices in the Institutionalization of Environmental Sustainability Policies in Higher Education Institutions - Flora D Canare (Chemical Engineering Transactions)
Understanding environmental sustainability within the context of the university is crucial for shaping future leaders, professionals, and policymakers aligning with the 2030 agenda and the Sustainable Development Goals (SDGs). A descriptive survey was utilized using situational analysis questionnaire to assess the strategic communication practices in the institutionalization of environmental sustainability policies. Participants demonstrated a commendable level of awareness, with a high mean score for initiatives such as Green Spaces and Biodiversity, Utilities Management, Waste Management, and Mainstreaming Environmental Sustainability. Moreover, the survey on preferred channels for communicating environmental sustainability policies and programs within the university community provides valuable insights into effective communication strategies. Results suggest a multifaceted approach combining traditional face-to-face methods with the extensive use of electronic/digital platforms and informative materials. The factors like "Accuracy and Quality of Information" and “Interactive” across various channels underscores the critical role of content reliability in sustainability communication. This study also noted that local Higher Education Institutions in Central Luzon, Philippines have limited institutional policies to advocate and promote environmental sustainability programs. Thus, this study also proposes strategies drawn from the initial result of this paper and from other relevant literature to enhance communication for environmental sustainability in tertiary higher education. By adopting these strategies, higher education institutions may not only instill a culture of sustainability but also empower future leaders to address the global challenges of environmental stewardship.